Penggunaan Media Berbasis Video untuk Meningkatkan Keaktifan Belajar dan Kemampuan Membaca Efektif pada Siswa Kelas VI Semester 1 di SDN 1 Rawa Laut - Saleh, Dentiana (STKIP PGRI Bandar Lampung, 2022)
This study aims to determine whether the use of the Letter Card teaching based Youtube video aids can improve the reading fluency and activity of sixth grade elementary school students in semester 2. The method in this study is a collaborative classroom action research involving researchers, peers (teachers) and school principals. This research was carried out in class VI, semester 2 of SDN 1 Rawa Laut, Enggal District, Bandar Lampung City for the 2020/2021 academic year with a total of 30 students. The focus of this research is the results of learning Indonesian and the effectiveness of using letter card props to improve reading fluency. This Classroom Action Research uses two cycles. Each cycle consists of three meetings, each meeting consists of four steps, namely planning, action, observation and reflection. The results showed an increase in student learning outcomes. This is evidenced by the students' reading fluency in cycle I and cycle II with the same SK / KD in the good category. Student activity also showed an increase in cycle I and cycle II in the very active category. By looking at the results of the study, it can be concluded that this research is able to answer the research objectives, namely the use of letter card display can improve reading fluency and activity of class VI students of SD Negeri 1 Rawa Laut, Enggal District, Bandar Lampung City for the 2020/2021 school year.